Neural Correlates of Liberalism and Conservatism in a Post-communist Country - Kremláček, Jan; Musil, Daniel; Langrová, Jana; Palecek, Martin (Frontiers in Human Neuroscience, 2019)
Previous results showed a strong correlation between conservatism/liberalism and brain activity linked to error response (r = 0.59, p<0.001) in the USA environment. We re-ran the experiment on a larger and age-homogeneous group (n = 100, 50 females and 50 males, aged 20-26 years) in the Czech Republic; a European country with different sociocultural environment and history. We did not find a relationship between the brain activity connected to conflict monitoring and self-reported conservatism/liberalism orientation (rho = -0.11, p = 0.297) or conservatism/liberalism validated for the USA agenda (rho = -0.01, p = 0.910). Instead of replicating the previous study we decided to test the hypothesis under a different socio-cultural context. Our results support a view of self-reported or validated, conservative or liberal attitudes as a complex behavioral pattern. Such a behavioral pattern cannot be determined with statistical significance, using a simple Go-NoGo detection task, without accounting for confounding factors like age and socio-cultural conditions. Sufficiently powered studies are warranted to evaluate this neuro-political controversy.